Ryan Quinn and the Rebel's escape - McGee, Ron (Harper, an imprint of HarperCollinsPublishers, 2016)
When his father disappears and his mother is abducted, Ryan learns that his missing parents are secret agents and that he must undertake a perilous mission to rescue them.